Interprofessional Care and Mental Health A Discursive Exploration of Team Meeting Practices (The Language of Mental Health, 2018)
This book utilises conversation analysis (CA) and discursive psychology (DP) methodologies to examine the internal workings of multi-disciplinary teams which are concerned with the care, treatment and diagnosis of clients with complex mental health needs. Bringing together practitioners, service users and researchers who were part of the MDTsInAction research project, the authors offer a unique and systematic investigation into the ways members of multidisciplinary teams collaboratively manage their shared goals. A particular focus is on the language used in team meetings, and how examination of meeting talk can help us better understand the practice of inter-professional working. The authors also describe how a range of institutional barriers and concerns needed to be tackled in implementing the study in a healthcare setting. Over the course of this book they reveal a number of methodological developments which will be of interest to researchers and academics in CA/DP, and in healthcare communication generally. This book highlights how CA and DP can be used to identify and improve communicative practices in a healthcare setting; and also serves as an example of how to conduct an applied CA/DP project in a way that achieves impact. Cordet Smart is a lecturer and clinical research tutor at the University of Plymouth, UK. She is the Principal Investigator on the MDTsInAction research programme. Her research includes interactions within clinical and group contexts and exploring the multiple presentations of social influence from a discursive psychology perspective. Timothy Auburn is Associate Professor in the School of Psychology at Plymouth University, UK. His research focuses on discursive psychology and social interaction, particularly in relation to institutional contexts such as the criminal justice system.